Dynamics of Demand for Rainfall Index Insurance : Evidence from a Commercial Product in India - Stein, Daniel (Published by Oxford University Press on behalf of the World Bank, 2020)
This paper analyzes the dynamic nature of rainfall insurance purchasing decisions. Customers of the Indan microfinance institution BASIX who receive an insurance payout are 9 to 22 percentage points more likely to purchase insurance the following year. This effect cannot be satisfactorily explained by trust, learning, or direct effects ofweather, leading to the conclusion that it is driven by behavioral effects. Overall, low repurchasing rates even after payouts suggest that the studied rainfall index insurance products are likely to continue struggling to achieve significant sales at market prices.